Integration of Botanical Pesticide and Entomopathogenic Fungi to Control the Brown Stink Bug Riptortus linearis F. (Hemiptera: Alydidae) in Soybean - Suharsono .; Yusmani Prayogo (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2014)
ABSTRACTIntegration of botanical pesticide and entomopathogenic fungi to control the brown stink bug Riptortus linearis F. (Hemiptera: Alydidae) in soybean. The efficacy of botanical pesticides i.e. Annona squamosa seed powder (ASP) or Jatropha curcas seed powder (JSP) integrated with entomopathogenic fungi, Lecanicillium lecanii to control brown stink bug, Riptortus linearis F. was studied at Muneng Research Station, the Indonesian Legume and Tuber Crops Research Institute (ILETRI) in June up to September 2011. The purpose of the research was to determine the efficacy of integration the natural pesticides i.e, A. squamosa seed powder (ASP) and Jatropha curcas seed powder (JSP) and entomopathogenic fungi L. lecanii to control brown stink bug. The treatments were application of (1) ASP 50 g/l, (2) JSP 50 g/l, (3) ASP 50 g/l + L. lecanii 107/ml, (4) JSP 50 g/l + L. lecanii 107/ml, (5) L. lecanii 107/ml, (6) deltametrin and (7) control (untreated). Application of ASP and JSP combined with L. lecanii decreased the hatched eggs by 84% and 82%, respectively. However, reduction of hactched egg from a single application of ASP and JSP were 56-61% . ASP and JSP combined with L. lecanii reduced both nymphs and adult stink bug population built up and damage (empty pod). Application of ASP and JSP in combination with L. lecanii did not affects the survival of generalist predators such as Paederus sp., Oxyopes sp. and Coccinella sp. as opposed to chemical insecticide that did. The integration of ASP or JSP with entomopthogenic fungi L. lecanii was able to increase the efficacy of brown stink bug control.